Soil & surface water management for profitable crops and pastures on waterlogged and saline land a final report prepared for the Grains Research and Development Corporation : GRDC project number DAW717 - Bakker, Derk Machiel; Western Australia. Department of Agriculture and Food.; Grains Research and Development Corporation (Australia) (Albany, W.A. : [Dept. of Agriculture and Food, 2007)
"The project investigated: a) the ability of raised beds to prevent waterlogging; b) enhance leaching; c) minimise capillary rise; d) reduce on-site recharge and e) restore profitable cropping and pasture growth on waterlogged and saline land [in Western Australia]." -- Project summary.
Cover title.
Bibliography: p. 1-3.
Keywords: Soils, Salts in -- Western Australia; Waterlogging (Soils) -- Western Australia; Soil management -- Western Australia